Market segmentation practices and performance of small and medium scale enterprises in Southwest, Nigeria - F. A, Babatola; P. O, Adeusi; E.M, Ogunjemilua; T A, Peters. (International Journal of Economics, Business and Management Studies, 2025)
This study investigates the relationship between market segmentation practices and performance of small and Medium –Scale Enterprises (SMEs) in Southwest, Nigeria. The study used descriptive survey research design, with the population of 23, 289 registered small and medium scale enterprises which cut across six (6) States in Southwest, Nigeria namely: Lagos State, Ogun State, Oyo State, Osun State, Ondo State, and Ekiti State. Taro Yamane formula 1968 was used to determine the sample size of 393 registered SMEs in the six States and multiple regression was used to analyze the stated hypotheses at a 5% level of significance. Findings shows that respondents acknowledge the importance of demographic factors, notably gender-based segmentation, in tailoring marketing strategies and identifying new market opportunities. The findings of the study also showed that there is significance relationship between geographical market segmentation and SMEs performance in Southwest, Nigeria (F=262.251, P=0.00 and R2=0.634). Also, demograhical market segmentation has significant effect on SMEs performance in SouthWest, Nigeria (F=77.650, P=0.00 and R=0.4072). The study concluded that geographic and demographic market segmentation affect the performance of small and medium sized enterprises in Southwest Nigeria. The study recommended that there is a need to encourage SMEs to develop strategies for adopting market segmentation practices to improve their performance.